2024
DOI: 10.1186/s12943-023-01926-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolving insights into the improvement of adoptive T-cell immunotherapy through PD-1/PD-L1 blockade in the clinical spectrum of lung cancer

Yutao Li,
Amit Sharma,
Ingo G.H. Schmidt-Wolf

Abstract: Undeniably, cancer immunotherapies have expanded the spectrum of cancer treatment, however, some patients do not respond to immunotherapies. This scenario is no different for lung cancer, whose two main types, non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC), still pose a serious clinical challenge. Adoptive T-cell therapies (ATC), which primarily include cytokine-induced killer (CIK) cell therapy, chimeric antigen receptor T-cell (CAR T-cell) therapy and γδ-T-cell therapy, strengthen the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 132 publications
0
0
0
Order By: Relevance
“…The PD-1/PD-L1 axis inhibits T cells in CAR-T-cell therapy for solid tumors, but disrupting this pathway is complex. One study revealed that the affinity between a CAR and its antigen is crucial for determining how susceptible T cells are to PD-1/PD-L1 inhibition [56], particularly in diseases such as lung cancer [57].…”
Section: Pd-1 and Pd-l1 Inhibitorsmentioning
confidence: 99%
“…The PD-1/PD-L1 axis inhibits T cells in CAR-T-cell therapy for solid tumors, but disrupting this pathway is complex. One study revealed that the affinity between a CAR and its antigen is crucial for determining how susceptible T cells are to PD-1/PD-L1 inhibition [56], particularly in diseases such as lung cancer [57].…”
Section: Pd-1 and Pd-l1 Inhibitorsmentioning
confidence: 99%